Financial Structure and Profitability of IFCI Ltd. : An Empirical Analysis - Pandey, Shishir (Indian Journal of Finance, 2012)
A company's Capital Structure determination constitutes a difficult decision that involves several antagonistic factors. Profitability is the main factor for consideration at the time of designing the capital structure of a firm. The purpose of this paper is to examine the extent to which growth determines the Capital Structure of IFCI Ltd. This is done by examining some component of capital structure in relation to IFCI Ltd. and then testing the resulting ideas empirically. This paper may provide useful insights for the interested parties, such as owners, investors etc.